Right To Work Reflected At Okky Madasari's The Years Of The Voiceless (2013): A Feminist Approach - Az Zahra, Fathiya; , Dr. Phil. Dewi Candraningrum, M.Ed; , Titis Setyabudi, S.S., M.Hum (2015)
The major problem of this study is how right to work is reflected in Okky Madasari's The Years of the Voiceless. The objective if this study is to analyze the novel based on the feminist analysis In analyzing The Years of the Voiceless, the writer uses qualitative method and feminist approach. The data sources consist of primary data and secondary data sources. The primary data source is the The Years of the Voiceless novel itself and the secondary data sources are the other sources related to the analysis such as the author's biography, some books and article related to the subject. The method of the data collection is library research. The technique of data analysis is descriptive analysis. The result of the study shows the following conclusion. Based on Feminist Approach, The Years of the Voiceless novel shows the right to work that happen in Sumarni as the major character in this novel.